Geological framework of the Bagnoli-Coroglio coastal zone and continental shelf, Pozzuoli (Napoli) Bay. Issue 6 (2nd July 2020) - Sacchi, M.; Matano, F.; Molisso, F.; Passaro, S.; Caccavale, M.; Di Martino, G.; Guarino, A.; Innangi, S.; Tamburrino, S.; Tonielli, R.; Vallefuoco, M.
ABSTRACT: Bagnoli-Coroglio is a Site of National Interest (SNI) facing the Pozzuoli Bay that has been the place of an industrial activity for more than a century (1854-1985). The modern coastal geology of this area results from the recent evolution of an antecedent volcanic landscape that originated after a caldera collapse following the eruption of Neapolitan Yellow Tuff (NYT) of Campi Flegrei (15 ka). After the NYT eruption, a shallow marine depression formed within the caldera collapse area that underwent progressive filling-up, due to volcaniclastic sediment input from the caldera borders, within a semi-enclosed source-to-sink system. The integrated interpretation of the Digital Terrain Model (DTM) of the Bagnoli-Coroglio area and the high resolution reflection seismic profiles acquired off the Pozzuoli Bay suggests that the present-day coastal plain of Bagnoli-Fuorigrotta and conterminous continental shelf represent the latest infilling phase of the annular depression (caldera 'collar') between the structural border of the NYT caldera and the inner caldera resurgent dome. The stratigraphic architecture and morpho-bathymetry of the Bagnoli inner shelf provide a record of the complex interplay between eustatic sea level changes, volcano-tectonic (ground/seafloor) deformation, and supply of volcaniclastic sediments, with associated coastline shifts over the last millennia.